Pengaruh Media Pembelajaran Gamifikasi Berbasis ICT Terhadap Kemampuan Pemahaman Matematis Siswa SMP - Khairunnisa Khairunnisa (REGRESI: Journal of Mathematics Education and Application, 2025)
The development of information and communication technology (ICT) has driven innovation in mathematics learning, one of which is through the use of gamification-based learning media. This study aims to identify the effect of ICT-based gamification learning media on students' understanding of mathematical concepts at the junior high school level. The research method used is SLR (Systematic Literature Review). Ten national journal articles were used in this study, all of which met the criteria set by the researcher and were published between 2018 and 2025. Examples of ICT learning media platforms in this article include Kahoot!, Quizizz, Word wall, Math Bilbul, and other platforms. Based on the literature review, it was found that the use of ICT-based gamified learning media can improve students' mathematical understanding. This is because it can attract attention, increase motivation, and encourage students to play an active role in understanding the learning material. Based on the analysis results, it can be concluded that ICT-based gamified learning media has the potential to be an innovative alternative in mathematics learning to improve students' understanding of mathematical concepts.